Caudal septoplasty: efficacy of a surgical technique-preliminnary report - Garcia,Leonardo Bomediano Sousa (2011)
Although not being the most frequent nasal septal deviations, those of the caudal septum account for many complaints. The correction of such defects has always been the subject of much controversy, and several different operative techniques have been described. AIM: To assess the efficacy of a surgical technique for correcting caudal septal deviations. MATERIALS AND METHODS: Prospective study with preliminary reports of 10 patients who answered a standardized, specific questionnaire (the Nasal Obstruction Symptom Evaluation, or NOSE), underwent acoustic rhinometry and had their noses photographed. Caudal deviations were then corrected through a surgical technique whereby the entire deviated portion is removed and a straight cartilage segment is placed between the medial crura of the alar cartilages, through a retrograde approach, to support the nasal tip. Sixty days after all patients were reassessed. RESULTS: As for the NOSE questionnaire, mean pre-operative and post-operative scores were 82.39 and 7.39 respectively (p<0.001). Pre-operative acoustic rhinometry showed mean minimum cross-sectional area (MCA) values of 0.352 and 0.431 cm2, whereas mean post-operative values were 0.657 and 0.711 cm2(p<0.0001). CONCLUSIONS: The study results prove, both subjectively (patient satisfaction as measured with a standardized questionnaire) and objectively (acoustic rhinometry findings), that the proposed technique for correction of caudal septal deviation is safe and effective.